2003
DOI: 10.1002/eji.200323678
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoblastoid cells express HLA‐B27 homodimers both intracellularly and at the cell surface following endosomal recycling

Abstract: The MHC class I allele HLA-B27 is very strongly associated with development of autoimmune spondyloarthritis, although the disease mechanism remains unknown. Class I molecules classically associate in the endoplasmic reticulum (ER) with g 2-microglobulin ( g 2 m) and antigenic peptides for cell surface expression and presentation to T cells. We have previously shown that HLA-B27 is capable of forming g 2 m-free disulfide-bonded homodimers in vitro. Here we show that HLA-B27 forms disulfide-bonded homodimers in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
186
2
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 49 publications
10
186
2
2
Order By: Relevance
“…This approach was based on using antibodies that recognized the B27 heterodimer or ␤ 2 m-free HLA class I heavy chains. In our study, we assumed that free B27 heavy chains arise at the cell surface from dissociation of the heterodimer, either directly or upon endosomal recycling (3). Whereas the possibility that some forms of ␤ 2 m-free heavy chains may escape the ER and reach the cell surface cannot be formally ruled out, this possibility has not been demonstrated and is unlikely because of impairment by quality control mechanisms operating in the assembly of class I MHC molecules (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach was based on using antibodies that recognized the B27 heterodimer or ␤ 2 m-free HLA class I heavy chains. In our study, we assumed that free B27 heavy chains arise at the cell surface from dissociation of the heterodimer, either directly or upon endosomal recycling (3). Whereas the possibility that some forms of ␤ 2 m-free heavy chains may escape the ER and reach the cell surface cannot be formally ruled out, this possibility has not been demonstrated and is unlikely because of impairment by quality control mechanisms operating in the assembly of class I MHC molecules (4).…”
Section: Discussionmentioning
confidence: 99%
“…However, since HC10 also reacts with unfolded heavy chains in monomeric form, the possibility that subtypes fail to form homodimers to an equal extent at the cell surface cannot be ruled out. Bird et al (3) showed that the S67 mutant failed to formed disulfide-linked homodimers, but still retained the capacity to form multimers. In our study, S67 showed the same behavior in the presence of exogenous peptide as Cys 67 -containing subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERAP1 shRNA were then cloned into a lentiviral plasmid for stable transduction of 2 HLA-B27-expressing cell lines (C1R.B27 and HeLa.B27). C1R.B27 cells were previously generated by transfection of HLA-B27 into C1R cells, an HLA-A/B-negative mutant B lymphoblastoid cell line (15). HeLa.B27 cells were generated by transduction of HLA-B27 into HeLa cells, a cell line derived from cervical cancer cells.…”
Section: Methodsmentioning
confidence: 99%
“…Lack of activation of the UPR in macrophages from B7-transgenic rats is consistent with evidence that HLA-B7 does not misfold and the hypothesis that the UPR may be involved in the pathogenesis of SpA-like disease in rats. Other unusual properties of HLA-B27 include the tendency to form cell-surface homodimers via a mechanism distinct from ER misfolding (7,12,13); these homodimers have been hypothesized to be recognized in vivo by leukocyte receptors and to exert immunoregulatory effects (14). HLA-B7 also forms cell-surface homodimers in human cells as well as rat cells, although these homodimers are less abundant with HLA-B7 than with HLA-B27 (7,9).…”
mentioning
confidence: 99%